Pemeliharaan Alat Keselamatan Kapal Liferaft dan Alat Pemadam Api Ringan Kapal TB. Rizaluta Patra 3202 oleh PT. Spectra Tirtasegara Line - Indriyani Indriyani; Elsa A. Stantika; Altril Rayendra; Dhimas R Hartanto (SAINTARA, 2023)
Shipping safety equipment is the most important part for the ship to support ship activities during the voyage, including the security and safety of the ship's crew, cargo, passengers and the ship itself. Maintenance of ship safety equipment must be carried out as a condition for ships to be able to sail / seaworthy in accordance with established regulations in order to reduce the risk of accidents while sailing. This study will discuss the maintenance of 2 (two) safety devices on board the TB Rizaluta Patra 3202 by PT Spectra Tirtasegara Line. The method named in this writing uses data collection methods which include observation methods, interview methods, documentation methods, and library research methods. as well as a qualitative descriptive method to find out the information needed. Based on the research results, the authors conclude that PT. Spectra Tirtasegara Line has carried out maintenance of liferaft safety equipment and fire extinguishers as well as carried out feasibility checks to support ship safety and security in order to reduce risks in the event of an accident, reduce technical problems when using / developing liferaft and also ready-to-use fire extinguishers if they occur emergency state.